2017
DOI: 10.1016/j.bbmt.2016.12.640
|View full text |Cite
|
Sign up to set email alerts
|

Post-Transplantation Cyclophosphamide after Bone Marrow Transplantation Is Not Associated with an Increased Risk of Donor-Derived Malignancy

Abstract: Post-transplant cyclophosphamide (PTCy) can be used for graft versus host disease (GVHD) prophylaxis alone or in combination with other agents and is associated with excellent rates of engraftment, acute and chronic GVHD, and an absence of post-transplant lymphoproliferative disease. No study has previously evaluated the risk for developing donor derived malignancy (DDM) in patients who receive PTCy. Giving chemotherapy in the immediate post-transplant period carries with it a theoretic risk of disturbing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…(11) PTCy results in low rates of graft-versus host disease, (12)(13)(14)(15) post-BMT lymphoproliferative disorder, (16) and donor derived malignancies. (17) However, despite cures in the majority of patients and low toxicity, the graft failure rate, albeit all with full host recovery, was 50% (one patient suffered secondary graft failure after the manuscript was published). In an attempt to decrease graft failure, we hypothesized that increasing the dose of total body irradiation (TBI) from 200 to 400 cGy before BMT would increase engraftment without increasing transplant-related morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…(11) PTCy results in low rates of graft-versus host disease, (12)(13)(14)(15) post-BMT lymphoproliferative disorder, (16) and donor derived malignancies. (17) However, despite cures in the majority of patients and low toxicity, the graft failure rate, albeit all with full host recovery, was 50% (one patient suffered secondary graft failure after the manuscript was published). In an attempt to decrease graft failure, we hypothesized that increasing the dose of total body irradiation (TBI) from 200 to 400 cGy before BMT would increase engraftment without increasing transplant-related morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action suggests an upregulation of T-reg lymphocytes (18). Moreover, PTCy has been associated with very low rates of post-transplant lymphoproliferative disorder (29), donor derived leukemia (30), and a low immunosuppressive burden after BMT (31). This approach has consistently been associated with low rates of grades III-IV acute GVHD and chronic GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…While there has been questioning of donor-derived malignancies (DDM) associated with PTCy, a recent retrospective study by the Hopkins group showed an extremely low proportion of patients with a DDM (4 out of 789) over a 10-year period, suggesting that PTCy does not appear to increase the risk of DDM. 108 However, the authors acknowledge the short follow-up period of their study and report the need for continued close monitoring of DDMs over a longer follow-up time.…”
Section: Perspectivesmentioning
confidence: 93%